Determinants of Financial Development - Huang, Y. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. This book examines the emergence of both financial markets and carbon markets, and provides an in-depth investigation on the fundamental determinants of financial development.